1988
DOI: 10.1016/0028-3932(88)90107-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attentional shifts: Implications for the role of polysensory mechanisms

Abstract: Simple reaction times to lateralized visual (Experiment 1) or auditory (Experiment 2) targets were studied in normal subjects. The targets were preceded by a visual or auditory cue located on the same (valid cue), or opposite (invalid cue) side as the subsequent target, or on both sides (neutral cue), with one of four cue target intervals. The validity of visual and auditory cues influenced the speed of response to the visual target but not to the auditory target. It is hypothesized that cross-modal cueing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
96
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 9 publications
17
96
4
Order By: Relevance
“…However, evidence regarding effects of spatial cues on sound detection is somewhat equivocal. Ofthe previous investigations of this issue (Bedard et al, 1993;Buchtel & Butter, 1988;Mazzuchi et al, 1983;Posner, 1978;Simon, 1967;Spence & Driver, 1994), only Spence and Driver's (1994) Experiment 8 was similar to the present study in that the effect of uninformative spatial cues on sound detection was examined. Because both automatic and voluntary processes may contribute to performance when informative cues are used (e.g., Miiller & Rabbitt, 1989), it is difficult to provide an explanation for the inconsistency in the results of such studies.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, evidence regarding effects of spatial cues on sound detection is somewhat equivocal. Ofthe previous investigations of this issue (Bedard et al, 1993;Buchtel & Butter, 1988;Mazzuchi et al, 1983;Posner, 1978;Simon, 1967;Spence & Driver, 1994), only Spence and Driver's (1994) Experiment 8 was similar to the present study in that the effect of uninformative spatial cues on sound detection was examined. Because both automatic and voluntary processes may contribute to performance when informative cues are used (e.g., Miiller & Rabbitt, 1989), it is difficult to provide an explanation for the inconsistency in the results of such studies.…”
Section: Discussionsupporting
confidence: 59%
“…An expectation ofobserving cuing effects for an auditory detection task might appear to be rather optimistic. However, although the results of studies that have examined the effect of a location cue on target-detection performance have been rather mixed (cue-validity effects have been reported by Bedard, Massioui, Pillon, & Nandrino, 1993, Mazzuchi, Cattelani, & Umilta, 1983, and Simon, 1967, but not by Buchtel & Butter, 1988, Posner, 1978, or Spence & Driver, 1994, studies offrequency selectivity have quite reliably shown an effect of frequency cues on the accuracy of target detection (Greenberg & Larkin, 1968;Dai, Scharf, & Buus, 1991;Johnson & Hafter, 1980;Macmillan & Schwartz, 1975;Penner, 1972;Scharfet aI., 1987;Schlauch & Hafter, 1991;Sorkin, Pastore, & Gilliom, 1968). In addition, Mondor et al (in press) have shown that RT to detect a target tone embedded within a sequence of distractor tones is affected by target-distractor similarity in both frequency and location.…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, spatial cues affected a pitch discrimination task only when the cue was informative, suggesting a more conscious or endogenous mechanism. This suggests that frequency may be automatically encoded during any auditory attention task, whereas the encoding of auditory spatial information is dependent on the specifics of the experimental procedure (see also Buchtel & Butter, 1988;Mondor & Zatorre, 1995;Rhodes, 1987;Woods, Alain, Diaz, Rhodes, & Ogawa, 2001). To date, this hypothesis has not received unequivocal support, however; Mondor, Zatorre, & Terrio (1998, Experiment 2) found that even when performing a task on an orthogonal dimension, both frequency and location cues influenced performance, even when they were uninformative.…”
Section: Relevance To the Theory Of Indispensable Attributes (Tia)mentioning
confidence: 99%
“…The effects of cross-modal cueing in exogenous attention were different: For example, Buchtel and Butter (1988) used visual and auditory exogenous cues and measured the response time for visual and auditory targets. The main finding of their study was that visual-but not auditory-targets were affected by the preceding visual cues.…”
Section: Introductionmentioning
confidence: 99%